Effects of a pain oriented biobehavioral therapeutic education program on brain plasticity and pain intensity in subjects with chronic musculoskeletal pain: a feasibility study of a randomized controlled trial - Di-Bonaventura, Silvia; Donado-Bermejo, Aser; Matesanz-García, Luis; Molina-Álvarez, Miguel; León-Hernández, José Vicente; Lizcano-Álvarez, Ángel; Lerma-Lara, Sergio; Nogales-Morales, Maximiliano; Molina, Nuria; Fernández-Carnero, Josué; Gurdiel-Álvarez, Francisco; Ferrer-Peña, Raúl (Frontiers in neuroscience, 2025)
BackgroundChronic pain significantly impacts the physical, emotional, and social wellbeing of individuals. Despite advances in treatments, chronic pain prevalence continues to rise, emphasizing the need for comprehensive therapeutic approaches.ObjectiveThis study aimed to evaluate the feasibility and preliminary effects of a one-month Pain Oriented Biobehavioral Therapeutic Education (POBTE) program on clinical outcomes for chronic primary musculoskeletal pain.MethodsIn a single-blind feasibility pilot of a randomized controlled trial, 16 participants were assigned to an intervention group receiving POBTE education and exercise (n = 8) or a control group (n = 8) participating in exercise only. Primary outcomes were pain intensity, measured by the Numeric Pain Rating Scale, and Brain-Derived Neurotrophic Factor (BDNF) plasma levels.ResultsThe intervention group showed a significant increase in BDNF levels from a mean of 2.174 at baseline to 3.063 at the end of treatment (p = 0.001, r = 0.63), with a non-significant reduction in pain intensity. Secondary outcomes, including anxiety, sleep quality, and physical activity, improved significantly. The results, however, should be interpreted cautiously due to the small sample size.ConclusionThe POBTE program appears feasible and acceptable, showing preliminary signals consistent with potential improvements in several clinical variables related to chronic pain management. These exploratory findings support the need for larger-scale, adequately powered trials.